Effects of Minimally Decorated and Visually Stimulating Classroom Settings on the Social Behavior of Grade 1 Learners: A Hidden Curriculum Perspective - Tandog, Ruelagin; Tandog, Virginia; Martinez, Shanice; Hallasgo, Shiana Joy; Zapanta, Edelveis; Gerigdig, Romlen Sheen; Escarlos, Gladys; Loren, Richie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of visually stimulating and minimally decorated classroom environments on the observable social behavior of Grade 1 learners, viewing classroom design as a component of the hidden curriculum. Anchored in Bronfenbrenner’s Ecological Systems Theory, Hidden Curriculum Theory, and principles of environmental psychology, the study investigated how classroom environments influence cooperation, peer interaction, sharing and turn-taking, classroom participation, and adherence to classroom routines and rules. A quasi-experimental within-subject crossover design was employed involving ten Grade 1 learners from Musuan Integrated School, Maramag, Bukidnon. Participants were exposed to both classroom conditions, and their behaviors were assessed using a Structured Classroom Observation Checklist adapted from established classroom observation frameworks. Data were analyzed using weighted mean, standard deviation, and the Wilcoxon Signed-Rank Test. The findings revealed that learners demonstrated more positive social behaviors in the visually stimulating classroom environment than in the minimally decorated classroom. Higher levels of cooperation, peer interaction, sharing and turn-taking, classroom participation, and adherence to classroom routines and rules were consistently observed in the visually stimulating setting. Statistical analysis further confirmed a significant difference between the two classroom conditions, indicating that classroom environment influenced learners’ observable social behavior. The study concluded that visually stimulating classroom environments promote social engagement, positive interaction, active participation, and behavioral regulation among Grade 1 learners. It recommends the use of meaningful and organized visual classroom elements and encourages further studies involving larger samples and diverse educational contexts. This study supports SDG 4 (Quality Education) by contributing evidence on the role of learning environments in enhancing learner development and educational experiences. It also relates to SDG 3 (Good Health and Well-Being) and SDG 11 (Sustainable Cities and Communities) by promoting supportive educational spaces that foster positive social behavior and well-being. The findings contribute to educational, institutional, and community sustainability by informing classroom design practices that support holistic learner development and positive social outcomes.
Keywords: Classroom Environment; Grade 1 Learners; Hidden Curriculum; Observable Social Behavior; Quasi-Experimental Design; Social Development; Visually Stimulating Classroom